To write <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn><mi>y</mi></mstyle></math> as a fraction with a common denominator, multiply by <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> .

Simplify terms.

Combine <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn><mi>y</mi></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> .

Combine the numerators over the common denominator.

Simplify the numerator.

Multiply <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>25</mn><mi>y</mi></mstyle></math> from <math><mstyle displaystyle="true"><mo>-</mo><mi>y</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn><mo>-</mo><mn>26</mn><mi>y</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn><mi>y</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mrow><mo>(</mo><mn>2</mn><mo>)</mo></mrow><mo>+</mo><mn>2</mn><mrow><mo>(</mo><mo>-</mo><mn>13</mn><mi>y</mi><mo>)</mo></mrow></mstyle></math> .

Multiply both sides by <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Simplify the left side.

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>2</mn><mrow><mo>(</mo><mn>2</mn><mo>-</mo><mn>13</mn><mi>y</mi><mo>)</mo></mrow></mrow><mrow><mn>5</mn></mrow></mfrac><mo>⋅</mo><mn>5</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Apply the distributive property.

Simplify the expression.

Multiply <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>13</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Reorder <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn><mi>y</mi></mstyle></math> .

Simplify the right side.

Multiply <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> from both sides of the inequality.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn><mi>y</mi><mo>≥</mo><mo>-</mo><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn><mi>y</mi><mo>≥</mo><mo>-</mo><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn></mstyle></math> . When multiplying or dividing both sides of an inequality by a negative value, flip the direction of the inequality sign.

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Cancel the common factor of <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mn>26</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

The result can be shown in multiple forms.

Inequality Form:

Interval Notation:

Do you know how to Solve the Inequality for y (4-y)/5-5y>=0? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.